Experimental investigation on the mechanical and interfacial properties of fiber-reinforced geopolymer layer on the tension zone of normal concrete. (19th December 2022) - Shirai, Kazutaka; Horii, Junta; Nakamuta, Koki; Teo, Wee
Highlights: Trial fiber-reinforced geopolymer (FRG) was mixed using Hokkaido local materials. FRG was subjected to compressive and tensile tests under various conditions. Flexural tests used FRG-normal strength concrete composite specimens. XRD, FTIR, and SEM analyses were carried out for the FRG samples. Abstract: This study aimed to understand the mechanical and interfacial properties of fiber-reinforced geopolymer (FRG) layer on the tension zone of normal concrete. A trial mix of FRG using local materials obtained in Hokkaido was investigated. Compression and splitting tensile tests on the FRG test pieces were conducted under different mixing procedures, constituents, volume fractions of the polyvinyl alcohol fiber, curing conditions, and ages. Flexural tests using FRG-normal strength concrete (NSC) composite specimens with different FRG layer thicknesses were carried out. By placing the FRG layer on the tension side of the composite specimen, the flexural strength and energy absorption were significantly increased. The flexural strength for the NSC alone was 3.5 MPa, while the FRG-NSC composite specimens showed higher flexural strengths of 6.1–6.6 MPa. Also, XRD, FTIR, and SEM analyses were carried out for the FRG samples.